Proverbs knowledge discovery in the virtual social network due to common knowledge of proverbs - Mendes, Armando B. (2010)
In a series of interviews, it was collected a heterogeneous set of several million relations of positive and negative knowledge that a group of thousands of people has about a set of circa twenty-two thousand Portuguese Proverbs. This is a unique source for socio-cultural analysis of the mechanisms of transmission of oral culture in geographic discontinuous spaces. We present in this article some results on the problem of finding a homomorphism between proverbial knowledge and geographical locations. To find this relation, we chose an approach based on the Analysis of social networks where the broadcast of oral culture, at least historically, could be interpreted as a trace of direct social contact between some of their users. We can simply give the Hamming Distance between two people by comparing their proverbial knowledge and, then, choose for every person only those relations to a peer where this distance is minimal. The resulting graph is analysed by a new Clique Analysis procedure, proposed in this work, design to work on very dense networks. The procedure was tested on a subset of data and we found that there are clusters where the neighbourhood relation inducted by the minimum Hamming Distance could be a reflex of the geographical distribution and of some migration flux of the Azorean population. When we compare the cliques with high geographic proximity, we found some proverbs which are good discriminators between the different clusters.